Pengaruh Teknik Pembesaran pada Kandang Close house Berbasis IoT Terhadap Bobot dan Karkas Ayam Broiler - Mei Sulistyoningsih; Reni Rakhmawati; Setyoningsih Wibowo (JURNAL ILMIAH AGRINECA, 2023)
The success of broiler production is expressed in the performance of broiler chickens. The appearance of broiler chickens is influenced by management. Fight management factors have an important role as a determinant of the success of broiler chicken farming. The purpose of this study was to analyze the effect of the enlargement technique using IoT-based Close house cages on bobo and broiler chicken carcasses. This research was conducted in Jumo Village, Kedungjati District, Grobogan Regency. The materials used in this study were: DOC broiler 2500, water, disinfectant, commercial ration feed, vaccine, vitachick, plastic curtain. The tools used are: IoT-based Close house cages, drinking bowls, feed bins, buckets, thermometers, digital scales. The research was carried out in a quantitative descriptive manner, namely the effect of using IoT in cages seen from the weight and carcass of the broiler chickens produced. The maintenance process in the research was carried out for 4 weeks. The results of the qualitative descriptive test obtained an average body weight of broiler chickens at 4 weeks, namely 1732.8 grams, including normal body weight. While the average serving of broiler chicken carcass is 70.3%, which is included in the normal carcass percentage.